Psychological strains and youth suicide in rural China - Zhang, Jie; Wieczorek, William F.; Conwell, Yeates; Tu, Xin Ming (Social science & medicine (1982), 2011)
The strain theory of suicide postulates that suicide is usually preceded by psychological strains. A strain can be a consequence of any of four conflicts: differential values, aspiration and reality, relative deprivation, and lack of coping skills for a crisis. This study, with a blend of psychiatric and social predictors of suicide, identified correlates of suicide that are relevant to Chinese culture and tested the strain theory of suicide with Chinese data. We sampled 392 suicides and 416 living controls (both aged 15–34 years) from 16 rural counties in China in 2008 and interviewed two informants for each suicide and each control. We found that marriage and religion/religiosity did not distinguish the suicides from the living controls among Chinese rural young women. Religion/religiosity tended to be stronger for suicides than for controls. Psychological strains in the forms of relative deprivation, unrealized aspiration, and lack of coping skills were significantly associated with suicide, even after accounting for the role of mental illness. The strain theory of suicide forms a challenge to the psychiatric model popular in the West, at least in explaining the Chinese suicide. ► One of the largest psychological autopsy studies in the world. ► Blend between psychiatric and social predictors of suicide. ► Theory testing with data from China. ► Marriage and religiosity are not protective factors of suicide in rural China. ► The strain theory of suicide as a challenge to the psychiatric model.